Efficacy of different Plant Extracts and Spinetoram (Radiant) Against Red Flour Beetle (Tribolium Castaneum (Herbst.) (Coleoptera: Tenebrionidae). - Rehman, Habib-Ur; Saleem, Ashiq; Bibi, Sadia; Ahmad, Ahmad; Muhammad , Waqas; Qazi, Imran; kareem, Yusra; Ahmad, Aftab; Khan, Imtiaz (Indus Journal of Bioscience Research, 2024)
Agriculture commodities infested by insect pest are being controlled by various methodologies for countering their drastic affects. One of the earliest methods is the use of insecticide against red flour beetle (Tribolium castaneum) insects have developed resistance against these insecticides, there for in the present research we were examine the mortality effect of two plants extracts (kaniar and shahtra) and spinetoram (radiant) against red flour beetle to compare the efficacy of these insecticide. The lethal effect of kaniar, shahtra and spinetoram were be evaluated using 6 concentrations 2.5, 5, 7.5, 10, 12.5 and 15 with 3 replications. The filter paper was used for bioassay evaluating the mortality after 24, 48, 72, and 96 hours. Statistical analysis was carried out for (ANOVA) using statistics 8 software. Mean of significant treatments were compared using Tukey HSD test. Mortality analysis showed that highest mortality was observed in case of spinetoram (radiant) (97%) at 150 ppm after 96-hour exposure following the plant extract Kaniar (70%) at 15% concentration after 96-hour exposure and shahtra (57%) at 15% concentration after 96-hour exposure, high repelancy was obtained by the plant extract, Shahtra (100%) after 60 minutes exposure followed by Kaniar (93%) after 60 min exposure. The results concluded that both the plants are highly effective than the insecticide against Tribolium castaneum and they can be safely used against stored product pests in commodities to conserve the food grains for future use without residual effects and other side effects related to health and food quality.